La corporeità nella psicoterapia online. Un’osservazione clinica - Gatti, Maria Gabriella (Il sogno della farfalla, 2021)
In this article the author analyses a clinical case about a patient reporting anorexic-cenesthopathic symptoms. During the psychotherapeutic practice the patient had manifested significant improvements. However, as a result of the covid-19 restrictions the psychotherapy was interrupted leading to a worsening of her conditions. This regression was rapidly solved once the therapeutic relationship was subsequently established during the online setting. This clinical case offers an opportunity to understand the role that corporeity plays in online psychotherapy. In this article the author sheds a new light on the two concepts of ‘body as subject’ and ‘body as object’ as classically defined by phenomenological psychopathology, offering a new interpretation according to the Human Birth Theory by Massimo Fagioli.